Yield of essential oil of and citral content in different parts of lemongrass leaves (Cymbopogon citratus (D.C.) stape) poaceae - Ming, L. C.; Figueiredo, R. O.; Machado, S. R.; Andrade, R. M.C. (International Society for Horticultural Science (ISHS), 1996)
Lemongrass (Cymbopogon citratus (DC,) Stapf.) is widely cultivated to obtain citral, a main component of the essential oil which is used in chemical industries. An experiment conducted at the Department of Horticulture, Agronomical Sciences Faculty, UNESP, Botucatu, Sao Paulo to evaluate yield of essential oil and citral content in the blade and sheath of leaves. The essential oil was extracted by hydrodis-tillation in a Clevenger apparatus. Citral content was analyzed by GC. Tissues of blades and sheathes were examined anatomically to observe secretary structures. Microchemical tests were made, with SUDANIV.